Fintech and SME FinanceFintech and the Future of Finance Flagship Technical Note Expanding Responsible Access (Other Financial Sector Study, 2022)
This technical note is structured in the following manner. Section two provides an overview of the main barriers and frictions that SMEs face to access finance. Section three explores how digitization is an enabler for SME finance and how different fintech solutions address these barriers. The fintech solutions analyzed include digital credit, asset-based lending, and equity products. Also examined are innovative products such as digital payments, credit risk assessment using alternative data, tokenized assets, and electronic invoicing. Market enablers such as e-commerce and open banking, and the digitization of business processes, which contribute to addressing the barriers and frictions to SME access to finance, are also highlighted. Section four analyzes how the providers of these fintech solutions for SMEs impact traditional banks, financial institutions, and implications on the financial market structure. This section also discusses the effects of the COVID-19 pandemic on the use of digital financial products for SMEs. Section five then addresses some of the key risks and challenges involved in the adoption of digital financial products and key market enablers. Finally, section six presents policy and regulatory recommendations to address the different challenges